Apoyo en la supervisión de obras civiles en la oficina de planeación de Belén, Boyacá (2023)
This article presents the report of the activities carried out as an intern at the Secretary of Planning of the Municipality of Belén, Boyacá, in the technical supervision of construction projects and civil works. For this purpose, the investigative methodology with a qualitative approach was used, taking into account that the accompanying activities for the execution of civil projects will be described, such as supervision of the execution of activities under compliance with technical and legal standards that guarantee quality. projects, verify the status of the yellow machinery available to the municipality, prepare budgets, amounts of work and Analysis of Unit Prices (APU) for the consolidation of contracts, prepare reports of visits made and progress of work and formulation of infrastructure projects that benefit the inhabitants of the municipality of Belén. With this internship, the aim is to reinforce and put into practice the knowledge acquired in the academy, based on real work situations, in which you demonstrate skills, abilities and human values to correctly carry out your work and guarantee the quality, efficiency and effectiveness of the processes that are part of Likewise, the intervention of the intern student in a public entity, allows him to acquire his initial work experience, which will be the pillar for his professional career and his successful performance in future jobs.